Use of the Glycolipopeptid Biosurfactant Produced by Lactiplantibacillus plantarum Tw226 to Formulate Functional Cinnamon Bark Essential Oil Emulsions - Virginia M. Lara; María F. Gliemmo; Marisol Vallejo; María del Carmen García González; María del Carmen Alfaro Rodríguez; Carmen A. Campos (Foods)
The stabilization of essential oils in emulsions using surfactants of natural origin is of significant interest, and the use of biosurfactants produced by lactic acid bacteria could be an alternative. In this study, the total and partial substitution of Tween 80 in cinnamon bark essential oil emulsions was proposed using a glycolipopeptide biosurfactant produced by Lactiplantibacillus plantarum Tw226. The oil-in-water emulsions formulated contained cinnamon bark oil at a concentration of 5 g/L, with Tween 80, the biosurfactant, or a mixture of both as the surfactant agent, reaching a final concentration of 5 g/L. Homogenization was performed using a high-speed homogenizer. The emulsion with both the biosurfactant and Tween 80 was classified as a nanoemulsion (Z-av < 200 nm) that was stable for eight weeks, while the one with only the biosurfactant was a mini-emulsion (200 > Z-av < 500 nm). Furthermore, the emulsion with a combination of surfactants exhibited antioxidant activity equal to that of the emulsion with only Tween 80 and higher than that of the emulsion with only the biosurfactant. The antifungal activities of the three emulsions against Candida tropicalis, Candida krusei, and Zygosaccharomyces bailii did not change, regardless of the surfactant used, according to MIC values. In conclusion, a mixture of biosurfactant and Tween 80 or biosurfactant alone is an alternative for reducing or substituting synthetic surfactants in essential cinnamon bark oil emulsions, depending on their desired physical and functional properties. This work amplifies the scarce knowledge of essential oil emulsions stabilized with biosurfactants produced by lactic acid bacteria.